Prevalence of color vision deficiency among primary school pupils in Duhok city, Kurdistan Region, Iraq - Azad Jameel Hussein; Samim Ahmed Al-Dabbagh (Advanced Medical Journal)
Background and objectives: Color vision deficiency or color blindness is a difficulty in recognizing certain colors. The color vision deficient persons remain unmindful about their condition and only become aware accidentally when tested for color vision. Color vision deficiency may affect job performance in certain careers like drivers, pilots, electrical and electronic engineers, policemen, artists, and medical practitioners. The study aims to detect the color vision deficiency prevalence among the primary school pupils in Duhok city.